Stefan Gandler: Marxismo crítico en México: Adolfo Sánchez Vásquez y Bolívar Echevarría, México D.F.: FCE/UNAM/Universidad Autónoma de Querétaro, 2007, 621 pp. - Águila, Levi Del (2008)
El artículo no presenta resumen.